Micron-scale flaky barium strontium titanate microcrystal powder and preparation method thereof
Based on the existing technology basis, the topological conversion method assisted by the salt method is used to prepare a micronicated micronic acid titanic acid with a high diameter thickness ratio and controlled size, which solves the complex and complicated preparation process in the existing technology. The problem of low yield has achieved efficient preparations for high -performance weaving ceramics and electronic devices.
Patent Information
- Application Number
- CN202411576716.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art is difficult to prepare micron-scale flake barium strontium titanate powder with high diameter and thickness ratio, controllable size, and adjustable components. The preparation process is complex and the yield is low, which affects its high-performance textured ceramics and electronic devices. Application in.
The topology chemical conversion method assisted by the salt method is used to prepare the BABI4TI4O15 front -drive body that meets the shape conditions of the sliced shape through the salt method, and then replace the ingredients to the required elements through the topological transformation method to generate a high diameter thickness ratio and strong and strong. Attractive micron -grade titanic acid titanic acid.
The preparation of micromi -grade titanic acid with a high diameter ratio of 10 and controlled size is more than 10, and the dimensions of the size of the size are simplified, the preparation cycle is shortened, the yield is increased, and it is suitable for high -performance weaving ceramics and new types. Preparation of electronic devices.
Smart Images

Figure CN119370885A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special functional powder material preparation, and specifically relates to a micron-level flaky barium strontium titanate microcrystalline powder and a preparation method thereof. Background Art
[0002] Barium strontium titanate is an important multifunctional material with wide applications in thermoelectric conversion, piezoelectric transducers, supercapacitors, microwave phase shifters, photoelectrocatalysis and other fields. Barium strontium titanate has a typical simple perovskite structure. Depending on the ratio of strontium to barium, the lattice structure is tetragonal or cubic. Due to its high lattice symmetry, the morphology of barium strontium titanate powder formed under normal conditions is spherical or cubic. The powder does not have anisotropy in microscopic morphology. In some special applications, such as the preparation of high-performance oriented ceramics and photoelectrocatalysis, barium strontium titanate powder is required to have a flaky microscopic morphology. It is difficult to prepare such micron-sized flaky powders by conventional synthesis methods. At present, the main process technologies that can realize the synthesis of flaky barium strontium titanate include hydrothermal method, sol-gel method, molten salt method, topochemical transformation method, etc. Among them, the flaky barium strontium titanate prepared by topochemical transformation method has the advantages of simple process, easy availability of raw materials, good product performance and high yield.
[0003] The topological chemical transformation method uses a layered perovskite-like flaky powder with a highly anisotropic lattice structure as a reaction precursor, and chemically reacts with a strontium / barium source under molten salt-assisted reaction conditions to generate strontium barium titanate flaky microcrystals that inherit the flaky micromorphology of the precursor. At present, it has been reported that flaky barium strontium titanate flaky powders are prepared by using flaky precursors such as Bi4Ti3O12 and Sr3Ti2O7 through a one-step or two-step chemical reaction process. However, the strontium barium titanate flaky powders prepared by the currently reported process methods have problems such as large powder thickness, low diameter-to-thickness ratio, difficulty in size control, difficulty in component control, and low yield, which limits the application expansion of flaky barium strontium titanate. In the prior art: a Chinese patent with publication number CN 106946566 A discloses a method for preparing a sheet-like barium strontium titanate powder material. Although the two-step method is also used, the chemical formula of the product barium strontium titanate is fixed, and the components cannot be adjusted, and it cannot be applied to various application requirements. In addition, the precursor prepared by the invention with publication number CN 106946566 A is Bi 4 Ti 3 O 12 The present invention selects BaBi 4 Ti 4 O 15The precursor is more stable and is not easy to produce impurities when preparing the sheet-like barium strontium titanate, and its preparation method is simpler and more efficient. At the same time, the sheet-like barium strontium titanate prepared by the invention with publication number CN 106946566 A has irregular morphology, great size difference, and is not stable enough, and cannot be well applied to textured ceramics.
[0004] Another example is a Chinese patent with publication number CN 103435341 A, which discloses a method for synthesizing ultra-thin micron-sized flaky barium strontium titanate crystals at low temperature. The flaky barium strontium titanate prepared by the method has very irregular morphology, huge differences in size, obvious impurities and huge quantities, which is very unfavorable for practical application. In addition, the preparation method is an ion exchange method, which has low efficiency, complicated process, high equipment requirements, and cannot achieve large-scale industrial production.
[0005] In view of the problems existing in the current preparation of flaky barium strontium titanate powder, the present application proposes a method for preparing flaky barium strontium titanate powder with high aspect ratio, controllable size and adjustable composition by a molten salt method-assisted topological chemical conversion method. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the present invention provides a micron-sized flaky barium strontium titanate powder and a preparation method thereof, which is prepared by a molten salt method-assisted topological chemical conversion method, and the microcrystalline material is a cubic or tetragonal perovskite structure.
[0007] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: to provide a micron-sized flaky barium strontium titanate microcrystalline powder, the crystal chemical formula of which is Ba 1-x Sr x TiO 3 , 0≤x≤0.95, its phase structure is a cubic or tetragonal perovskite structure; the crystal is a thin flake single crystal with a thickness of 0.2-0.7μm, a radial size of 3-10μm, and a diameter-to-thickness ratio greater than 10.
[0008] At the same time, a method for preparing the micron-sized flaky barium strontium titanate microcrystalline powder as described above is provided, which is prepared by a molten salt method-assisted topological chemical conversion method, comprising the following steps: Will Precursor powder and BaCO 3 Powder, SrCO 3 Powder or BaCO 3 and SrCO 3 The mixed powders are mixed in a molar ratio, an equal mass of molten salt is added, and ball milling is performed to obtain a mixed material containing a precursor; The mixture containing the precursor is kept at 900-1100° C. for 1-5 hours to obtain a reaction product; The reaction product was placed in deionized water, and the molten salt in the sintered product was removed by magnetic stirring combined with ultrasonic cleaning.3 After titration without precipitation, a sintered product free of salt is obtained; The salt-free sintered product is pickled to remove the by-products produced in the reaction; after the pickling, stirring water washing and ultrasonic water washing are performed to remove the residual HNO 3 The nitrate produced by the reaction is dried and washed to obtain a precipitate, i.e., micron-sized flaky barium strontium titanate microcrystalline powder.
[0009] Further, preparation The precursor powder comprises the following steps: according to BaBi 4 Ti 4 O 15 Stoichiometric ratio of BaCO3 powder, Bi 2 O 3 Powder, TiO 2 The powder is mixed with an equal mass of molten salt to obtain a mixture, and the mixture is kept at 850°C to 1050°C for 1 to 4 hours to obtain a calcined product; The calcined product was stirred and washed with deionized water to remove the molten salt in the calcined product until the supernatant was AgNO 3 Titration without precipitation; ultrasonic separation is used to separate the product after cleaning, so that the grains of different sizes in the product are separated, and the precipitate is obtained after the tiny particles with a length of less than 1 μm are removed by precipitation, and the precipitate is dried to obtain Precursor powder.
[0010] Furthermore, the molten salt used to obtain the calcined product is one of KCl and NaCl or a mixture of the two.
[0011] Furthermore, when the mixture is heated to the holding temperature, the heating rate is 5°C / min to 10°C / min.
[0012] Furthermore, the Precursor powder and BaCO 3 and SrCO 3 The molar ratio of the mixed powder ranges from 1:3 to 1:5; Furthermore, BaCO3 powder, Bi 2 O 3 Powder, TiO 2 The powder is mixed with an equal mass of molten salt by ball milling. Precursor powder and BaCO 3 Powder, SrCO 3 Powder or BaCO 3 and SrCO 3 The mixed powders were mixed by ball milling, and the mixing time was 12 h.
[0013] Furthermore, when the mixture containing the precursor is kept warm, the heating rate to the holding temperature is 3°C / min to 10°C / min.
[0014] Furthermore, dilute nitric acid is used for pickling the salt-free sintered product, and the concentration of the dilute nitric acid is 1 mol / L~3 mol / L.
[0015] In addition, the invention provides an application of the micron-sized flaky barium strontium titanate microcrystalline powder, specifically as a seed crystal template for preparing high-performance textured ceramics or for preparing electronic devices.
[0016] Compared with the prior art, the present invention has at least the following beneficial effects: a micron-sized flaky barium strontium titanate microcrystalline powder prepared by the present invention is prepared by a two-step method, which simplifies the preparation process, shortens the preparation cycle, and saves the preparation time cost under the premise of ensuring the quality of the template; the present invention first uses a molten salt method to prepare a precursor that meets the flaky shape conditions, and then replaces the components with the required elements by a topochemical transformation method without changing the shape. The micron-sized flaky barium strontium titanate microcrystalline powder prepared by the present invention has a flaky morphology, a large diameter-to-thickness ratio and strong orientation, a radial length of 2 to 10 μm, a thickness of 0.2 to 0.7 μm, a diameter-to-thickness ratio greater than 10, and a small size, which is an ideal template grain. The raw materials selected by the present invention are low in price, cost-controllable, and easy to industrialize. The micron-sized flaky barium strontium titanate microcrystalline powder of the present invention has a positive effect on the preparation of seed crystal templates for high-performance textured ceramics, and can also be used for new electronic devices and advanced sensors.
[0017] Furthermore, the present invention adopts the molten salt method to prepare the BBTO precursor, which can realize the synthesis of materials at a lower temperature, thereby simplifying the preparation process; at the same time, it more effectively utilizes the raw materials and reduces the generation of by-products and waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the XRD spectrum of the BaBi4Ti4O15 (BBTO) flake precursor prepared in Example 1.
[0019] Figure 2 This is the SEM image of the BaBi4Ti4O15 (BBTO) flake precursor prepared in Example 1.
[0020] Figure 3 This is the XRD pattern of BST microcrystals prepared in Example 2.
[0021] Figure 4 This is the SEM image of the BST microcrystals prepared in Example 2. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] In this application, if there is no special explanation, all the embodiments and preferred implementation methods mentioned in this application can be combined with each other to form a new technical solution. Unless otherwise specified, the professional and scientific terms used in this application have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content can also be applied to this application.
[0024] Example 1 Step 1, synthesis of precursors: according to BaBi 4 Ti 4 O 15 (BBTO for short) flake precursor reaction equation calculation, accurately weigh BaCO 3 (Purity 99.9%) 3.0616g, Bi 2 O 3 (Purity: 99.99%) 6.4899g, TiO 2 (purity: 99.99%) 21.1373g, NaCl (purity: 99.99%) 16.8061g and KCl (purity: 99.99%) 13.1968g; NaCl, KCl and ethanol 20mL, ZrO 2 30 g of BaCO was mixed and milled for 12 h, and then dried in an oven at 70 °C to obtain 30 g of salt mixture; 3 、Bi 2 O 3 、TiO 2 and molten salt with 60mL of ethanol, ZrO 2 The mixture was ball-milled for 12 h and dried in an oven at 70°C to obtain a raw material mixture; Step 2, keeping the mixture obtained in step 1 at 850° C. for 1 h at a heating rate of 5° C. / min to obtain a mixed product; Step 3: The mixed product obtained in step 2 is stirred and washed with hot deionized water to remove the molten salt in the sintered product until the supernatant AgNO3 There was no precipitation in the titration, indicating that the molten salt in the product was completely removed and BBTO precipitate was obtained; Step 4, adding hot deionized water to the BBTO precipitate obtained in step 3, and performing ultrasonic washing to separate grains of different sizes in the product, and after removing tiny particles by precipitation, drying the precipitate to obtain a BBTO precursor powder of uniform size; Step 5, synthesis of BST microcrystals: accurately weigh BaCO 3 (Purity 99.9%) 3.7235 g, SrCO 3 (purity: 99.99%) 5.5754 g, BBTO (purity: 100%) 60.8094 g, KCl (purity: 99.99%) 60 g, BaCO 3 、SrCO 3 , BBTO, KCl and 70 mL of ethanol, ZrO 2 The mixture was ball-milled for 12 h and dried in an oven at 70°C to obtain a mixture containing the precursor; Step 6, keeping the mixture obtained in step 5 at 900° C. for 1 hour at a heating rate of 5° C. / min to obtain a mixed product; Step 7, crushing the mixed product obtained in step 6, stirring and washing with hot deionized water to remove the KCl molten salt in the product, and repeating the washing until the supernatant AgNO3 is titrated without precipitation to obtain a salt-free sintered product; Step 8: Place the salt-free product obtained in step 7 in a 3 mol / L diluted HNO 3 The product is washed to remove the Bi generated in the reaction. 2 O 3 After the acid wash, the product was washed with magnetic stirring for 3 times and ultrasonic washing for 3 times to remove the residual HNO 3 and the nitrate produced by the reaction; after washing and drying, the target product, micron-sized flaky barium strontium titanate microcrystalline powder (BST), can be obtained. The chemical composition of BST microcrystalline is Ba 0.626 Sr 0.374 TiO 3 , showing a tetragonal perovskite structure; the grain size is about 2.75μm long and about 0.23μm thick.
[0025] Example 2 Step 1, synthesis of precursors: according to BaBi 4 Ti 4 O 15 (BBTO) flake precursor reaction equation calculation, accurately weigh BaCO 3 (Purity 99.9%) 4.0822 g, Bi 2 O3 (Purity: 99.99%) 8.6532 g, TiO 2 (purity: 99.99%) 28.1831 g, NaCl (purity: 99.99%) 40 g; BaCO 3 、Bi 2 O 3 、TiO 2 and molten salt with ethanol 80ml, ZrO 2 The mixture was ball-milled for 12 h and dried in an oven at 70°C to obtain a raw material mixture; Step 2, keeping the mixture obtained in step 1 at 1050° C. for 4 hours at a heating rate of 10° C. / min to obtain a mixed product; Step 3: The mixed product obtained in step 2 is stirred and washed with hot deionized water to remove the molten salt in the sintered product until the supernatant AgNO 3 There was no precipitation in the titration, indicating that the molten salt in the product was completely removed and BBTO precipitate was obtained; Step 4, adding hot deionized water to the BBTO precipitate obtained in step 3, and performing ultrasonic washing to separate grains of different sizes in the product, and after removing tiny particles by precipitation, drying the precipitate to obtain a BBTO precursor powder of uniform size; Step 5, synthesis of BST microcrystals: accurately weigh BaCO 3 (Purity 99.9%) 24.8235 g, SrCO 3 (purity: 99.99%) 37.1695g, BBTO (purity: 100%) 81.0792g, KCI (purity: 99.99%) 70g, BaCO 3 、SrCO 3 With 100mL of ethanol, ZrO 2 The mixture was mixed with 100 g of ball and ball-milled for 12 h. After the ball-milling, BBTO and KCl were added and ball-milled for another 1 h. The mixture was dried in an oven at 70° C. to obtain a mixture.
[0026] Step 6, keeping the mixture obtained in step 5 at 1000° C. for 5 hours at a heating rate of 10° C. / min to obtain a mixed product; Step 7, crushing the mixed product obtained in step 6, stirring and washing with hot deionized water to remove the KCl molten salt in the product, and repeating the washing until the supernatant AgNO3 is titrated without precipitation to obtain a salt-free sintered product; Step 8: Place the salt-free product obtained in step 7 in a 2 mol / L diluted HNO 3 The product is washed to remove the Bi generated in the reaction. 2 O 3After the acid wash, the product was washed with magnetic stirring for 3 times and ultrasonic washing for 3 times to remove the residual HNO 3 After washing and drying, the target product, micron-sized flaky barium strontium titanate microcrystalline powder (BST), can be obtained. BST microcrystalline has a cubic perovskite structure and the chemical formula is Ba 0.453 Sr 0.547 TiO 3 The grain size is about 9.32 μm in length and 0.81 μm in thickness.
[0027] Example 3 Step 1, synthesis of precursors: according to BaBi 4 Ti 4 O 15 (BBTO) flake precursor reaction equation calculation, accurately weigh BaCO 3 (Purity 99.9%) 4.0822 g, Bi 2 O 3 (Purity: 99.99%) 8.6532 g, TiO 2 (purity: 99.99%) 28.1831 g, NaCl (purity: 99.99%) 40 g; BaCO 3 、Bi 2 O 3 、TiO 2 and molten salt with ethanol 80mL, ZrO 2 The mixture was ball-milled for 12 h and dried in an oven at 70°C to obtain a raw material mixture; Step 2, keeping the mixture obtained in step 1 at 950° C. for 2.5 h at a heating rate of 8° C. / min to obtain a mixed product; Step 3: The mixed product obtained in step 2 is stirred and washed with hot deionized water to remove the molten salt in the sintered product until the supernatant AgNO 3 There was no precipitation in the titration, indicating that the molten salt in the product was completely removed and BBTO precipitate was obtained; Step 4, adding hot deionized water to the BBTO precipitate obtained in step 3, and performing ultrasonic washing to separate grains of different sizes in the product, and after removing tiny particles by precipitation, drying the precipitate to obtain a BBTO precursor powder of uniform size; Step 5, synthesis of BST microcrystals: accurately weigh BaCO 3 (Purity 99.9%) 3.999g, SrCO 3 (purity: 99.99%) 8.9836g, BBTO (purity: 100%) 81.6510g, KCl (purity: 99.99%) 90g, BaCO 3 、SrCO3 With 100mL of ethanol, ZrO 2 The mixture was mixed with 100 g of ball and ball-milled for 12 h. After the ball-milling, BBTO and KCl were added and ball-milled for another 1 h. The mixture was dried in an oven at 70° C. to obtain a mixture.
[0028] Step 6, keeping the mixture obtained in step 5 at 1100° C. for 3 hours at a heating rate of 3° C. / min to obtain a mixed product; Step 7, crushing the mixed product obtained in step 6, stirring and washing with hot deionized water to remove the KCl molten salt in the product, and repeating the washing until the supernatant AgNO3 is titrated without precipitation to obtain a salt-free sintered product; Step 8: Place the salt-free product obtained in step 7 in a 1 mol / L dilute HNO 3 The product is washed to remove the Bi generated in the reaction. 2 O 3 After the acid wash, the product was washed with magnetic stirring for 3 times and ultrasonic washing for 3 times to remove the residual HNO 3 After washing and drying, the target product, micron-sized flaky barium strontium titanate microcrystalline powder (BST), can be obtained. The BST microcrystalline has a cubic perovskite structure and the chemical formula is Ba 0.476 Sr 0.524 TiO 3 The grain size is about 9.98 μm in length and 0.76 μm in thickness.
[0029] like Figure 2 As shown in the SEM image, the prepared BBTO precursor crystals have similar morphology, uniform size, and no tiny grains, indicating that the method described in this application can obtain high-quality pure BBTO, which is ready for the subsequent synthesis of BST crystals. Figure 1 As shown in the XRD spectrum, the precursor product of this example corresponds to the standard card peaks one by one, indicating that a pure phase BBTO precursor is synthesized.
[0030] like Figure 4 As shown in the SEM image, the prepared and synthesized flaky barium strontium titanate crystals have similar morphology, are relatively uniform in size, and have few tiny grains, indicating that the method described in this application can obtain high-quality pure target product BST. Figure 3As shown in the XRD spectrum, the product of this embodiment corresponds to the standard card peak one by one, indicating that the pure phase target product BST is synthesized. The two-step synthesis method of the present application minimizes the appearance of impurities, greatly simplifies the process flow for preparing pure BST, and shortens the preparation time. At the same time, the present application cleverly prepares high-aspect-ratio flaky barium strontium titanate crystals by combining the molten salt method with the topochemical conversion method. The high-aspect-ratio flaky barium strontium titanate crystals can better orient the ceramic grains when preparing textured ceramics, directly determine the texture degree of the textured ceramics, and play a decisive role in the electrical properties of the textured ceramics.
[0031] After testing, the BST prepared in each embodiment of the present application has good electrical properties, meets the expectations of the invention, and can be well used in the preparation of textured ceramics and other electronic components.
[0032] Due to its various properties, barium strontium titanate materials are widely used in ceramic capacitors, thermoelectric elements, thermistors, memory, sonar, inverters, electrostatic transformers, dielectric amplifiers, infrared detection elements, memory materials, semiconductor materials, etc. Due to its excellent piezoelectric effect, barium titanate is widely used in energy conversion, signal conversion, oscillation based on piezoelectric equivalent circuits, sensor devices, microwave and sound conversion, etc. For example, piezoelectric lighters and detonators are manufactured by using the piezoelectric effect of piezoelectric ceramics to convert mechanical energy into electrical energy. Barium strontium titanate has a unique positive temperature coefficient effect. When the temperature rises, the resistance will increase sharply. It can be used in automobile engine starters, temperature sensors, overheat protectors, color TV automatic degaussers, refrigerator compressor starters, etc. In addition, barium strontium titanate materials can be used in tumor treatment, wound repair, and bacterial removal.
[0033] In summary, the present invention relates to a micron-sized flaky barium strontium titanate crystal and a preparation method thereof. During the preparation, BaBi is first prepared by a molten salt method. 4 Ti 4 O 15 The precursor BBTO and BaCO are converted into flake-like microcrystals by topochemical transformation. 3 、SrCO 3 The mixed powder is mixed, sintered at high temperature, and then washed with water and acid to remove by-products in the sintered product to obtain strontium barium titanate flake microcrystals with a crystal chemical formula of Ba 1-x Sr x TiO 3, 0≤x≤0.95, its phase structure is a cubic or tetragonal perovskite structure; the crystal is a thin single crystal with a thickness of 0.2-0.7μm and an aspect ratio greater than 10; the flaky barium strontium titanate microcrystals prepared by the method of the present invention have a high aspect ratio, and can achieve a wide range of adjustment of chemical composition and microcrystal size. The application of topological chemical transformation method is more conducive to the formation of pure BST with uniform size; the flaky barium strontium titanate microcrystals of the present application have uniform size, regular morphology, and good electrical properties. The method is simple in process, the raw materials are cheap, and the product yield is high; the product can; the flaky barium strontium titanate microcrystals prepared by the present invention can be used as a seed template for preparing high-performance textured ceramic materials, which has a positive effect on improving the density, orientation and comprehensive performance of textured ceramics, and can also be used in new electronic devices and advanced sensors.
[0034] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A micron-sized flaky barium strontium titanate microcrystalline powder, characterized in that: The crystal chemical formula is Ba 1-x Sr x TiO3, 0≤x≤0.95, its phase structure is a cubic or tetragonal perovskite structure; the crystal is a thin flake single crystal with a thickness of 0.2-0.7μm, a radial size of 3-10μm, and a diameter-to-thickness ratio greater than 10.
2. The method for preparing micron-sized plate-like barium titanate-based crystals according to claim 1, characterized in that: The preparation is carried out by a molten salt-assisted topological chemical conversion method, which includes the following steps: Will The precursor powder is mixed with BaCO3 powder, SrCO3 powder or mixed powder of BaCO3 and SrCO3 in a molar ratio, and an equal mass of molten salt is added, and ball milling is performed to obtain a mixture containing the precursor; The mixture containing the precursor is kept at 900-1100° C. for 1-5 hours to obtain a reaction product; The reaction product is placed in deionized water, and the molten salt in the sintered product is removed by magnetic stirring combined with ultrasonic cleaning, and a salt-free sintered product is obtained after the supernatant AgNO3 is titrated without precipitation; The salt-free sintered product is pickled to remove by-products produced in the reaction; after the pickling, it is washed with stirring and ultrasonic water to remove residual HNO3 and nitrates produced by the reaction, and the precipitate obtained after drying and washing is micron-sized flaky barium strontium titanate microcrystalline powder.
3. The method for preparing micron-sized flaky barium titanate-based crystals according to claim 2, characterized in that: preparation The precursor powder comprises the following steps: 15 BaCO3 powder, Bi2O3 powder and TiO2 powder in a stoichiometric ratio are mixed with an equal mass of molten salt to obtain a mixture, and the mixture is kept at 850°C to 1050°C for 1 to 4 hours to obtain a calcined product; The calcined product was stirred and washed with deionized water to remove the molten salt in the calcined product, and the supernatant was washed until no precipitation was found by AgNO3 titration; the washed product was separated by ultrasonication to separate the grains of different sizes in the product, and the precipitate was obtained after the micro-particles with a length of less than 1 μm were removed by precipitation, and the precipitate was dried to obtain Precursor powder.
4. The method for preparing micron-sized flaky barium titanate-based crystals according to claim 3, characterized in that: The molten salt used to obtain the calcined product is one of KCl and NaCl or a mixture of the two.
5. The method for preparing micron-sized flaky barium titanate-based crystals according to claim 3, characterized in that: When the mixture is heated to the holding temperature, the heating rate is 5°C / min~10°C / min.
6. The method for preparing micron-sized flaky barium titanate-based crystals according to claim 2, characterized in that: Said The molar ratio of the precursor powder to the mixed powder of BaCO3 and SrCO3 ranges from 1:3 to 1:
5.
7. The method for preparing micron-sized flaky barium titanate-based crystals according to claim 2, characterized in that: BaCO3 powder, Bi2O3 powder, TiO2 powder and molten salt of equal mass are mixed by ball milling. The precursor powder was mixed with BaCO3 powder, SrCO3 powder or BaCO3 and SrCO3 mixed powder by ball milling, and the mixing time was 12 hours.
8. The method for preparing micron-sized flaky barium titanate-based crystals according to claim 2, characterized in that: When the mixture containing the precursor is kept warm, the heating rate to the holding temperature is 3°C / min~10°C / min.
9. The method for preparing micron-sized flaky barium titanate-based crystals according to claim 2, characterized in that: Dilute nitric acid is used for pickling of salt-free sintered products, and the concentration of dilute nitric acid is 1mol / L~3mol / L.
10. The use of the micron-sized flaky barium strontium titanate microcrystalline powder according to claim 1, characterized in that: It can be used as a seed template for preparing high-performance textured ceramics or for preparing electronic devices.
Citation Information
Patent Citations
Method used for low-temperature synthesis of ultrathin micron sheet-shape barium strontium titanate crystal
CN103435341A
Preparation method of sheet shape barium strontium titanate powder material
CN106946566A